Handover decision with multi-access edge computing in 6G networks: A survey - Saeid Jahandar; Ibraheem Shayea; Emre Gures; Ayman A. El-Saleh; Mustafa Ergen; Mohammad Alnakhli (Results in Engineering)
Multi-Access Edge Computing (MEC) is a key technology in the evolution of mobile networks, especially for fifth and sixth generation (5G and 6G). MEC optimises communication and computational resources by hosting application processes close to the user equipment (UE) at the network edge, improving communication reliability and stability while reducing latency. A key feature of MEC is its ultra-low latency response, enabling real-time applications in next-generation networks. However, the mobility of UEs and the limited coverage of edge servers can lead to frequent handovers during the offloading process. As a result, advanced handover management strategies are required to jointly optimise handover and computation offloading. This paper provides a comprehensive overview of handover decision making in MEC systems, with particular emphasis on the challenges and solutions associated with the integration of communication, computation and mobility management. We examine the current state of research, provide an analysis of existing studies, and identify key gaps in the literature. The novelty of this work lies in its holistic approach to exploring the interdependencies between handover management, mobility control and computation offloading, while proposing future research directions. This work provides a forward-looking perspective on how these interrelated issues are likely to evolve, particularly in the context of future mobile networks using MEC technology.